Orthography, phonology, morphology, and meaning - Frost, Ram; Katz, Leonard (Advances in psychology (Amsterdam, Netherlands), 1992)
The area of research on printed word recognition has been one of the most active in the field of experimental psychology for well over a decade. However, notwithstanding the energetic research effort and despite the fact that there are many points of consensus, major controversies still exist. This volume is particularly concerned with the putative relationship between language and reading. It explores the ways by which orthography, phonology, morphology and meaning are interrelated in the reading process. Included are theoretical discussions as well as reviews of experimental evidence by leading researchers in the area of experimental reading studies. The book takes as its primary issue the question of the degree to which basic processes in reading reflect the structural characteristics of language such as phonology and morphology. It discusses how those characteristics can shape a language's orthography and affect the process of reading from word recognition to comprehension. Contributed by specialists, the broad-ranging mix of articles and papers not only gives a picture of current theory and data but a view of the directions in which this research area is vigorously moving.